Pengaruh Ukuran Pemerintah, Pertumbuhan Ekonomi dan Belanja Modal terhadap Kemandirian Keuangan Daerah - Warman, Aditia; Arza, Fefri Indra (Jurnal Nuansa Karya Akuntansi, 2024)
This study aims to determine the effect of the size local government, economic growth and capital expenditure on regional financial independence. The population of this survey for the period 2017-2021 consists of the regencies and localities located in the West Sumatra province. The current inquiry utilizes data obtained from secondary sources. Over the course of five years, a sample of nineteen districts/cities was compiled utilizing the Total Sampling technique. In order to analyze the data, multiple linear regression was applied. The study's findings indicate that regional financial independence is adversely affected by the magnitude of the local government and capital expenditures. Concurrently, regional financial autonomy is fostered by economic expansion.